PENERAPAN STRICT LIABILITY OLEH PERUSAHAAN DALAM RANGKA KONSERVASI LINGKUNGAN HIDUP DI INDONESIA - Muhammad Ainurrasyid Al Fikri; Fatma Ulfatun Najicha; I Gusti Ayu Ketut Rachmi Handayani (Indonesian State Law Review, 2022)
Strict liability is absolute responsibility imposed on perpetrators of environmental violations that result in losses to both the environment and the community around the environment. The research used in this paper is juridical normative and uses a statutory approach, a conceptual approach and a case approach. The development of strict liability in positive law in Indonesia has experienced development and refinement over time, indicated by the application made in several cases concerning environmental violations by several irresponsible parties. Basically, the implementation of strict liability really helps the aggrieved parties, especially the common people, in enforcing environmental laws in Indonesia.